Estudo da resistência de interface solo-geossintético pelo ensaio de rampa - Damasceno, Isabelle Gondim (Universidade Federal Rural do Semi-Árido, 2017)
The use of geosynthetics to improve the support of the structure of the slope, for example through reinforcement, is increasingly present in engineering works. Thus, the constructs require a greater study on the behavior of soil-geosynthetic interaction. So, the various types of geosynthetics were cited, terminology, physical characteristics, composition, mechanical properties and durability. But, the main object of this study is the geogrid. Therefore, the present work objectives to analyze the soil-geogrid interface for reinforced soil through the ramp test. Also, make an apparatus that can perform the test and test it if is reliable. The research is experimental because it has equipment built and tested for it. In the scientific literature there are several published works on the subject, making a bibliographic review interesting for the base of this research, characterizing an exploratory-descriptive research. For this, an exploratory-descriptive research was carried out and it was possible to know more about what they had studied in relation to the reinforcement of soils with geosynthetics. At the same time, soil characterization tests were carried out. According to the results, there was a 31.43% increase in the interface resistance with the introduction of geogrid in the specific soil. Soon, the importance of these synthetic materials is perceived for various applications and the benefits that the construction gains with the use of this technique, as a better cost and ease of execution.
Monografia
Keywords: Geossintético; Interface; Atrito; Solo Reforçado; Tensão Cisalhante.; Geosynthetics; Interface; Friction; Reinforced soil; Shear Tension; ENGENHARIAS::ENGENHARIA CIVIL